Aid, Natural Disasters and the Samaritan’s Dilemma - Raschky, Paul A.; Schwindt, Manijeh (2012)
This paper discusses the impact of foreign aid on the recipient country's preparedness against natural disasters. The theoretical model shows that foreign aid can have two opposing effects on a country's level of mitigating activities. In order to test the theoretical propositions, the authors analyze the effect of foreign aid dependence on ex-ante risk-management activity proxied by the death toll from major storms, floods and earthquakes occurring worldwide between 1980 and 2002. They find evidence that the crowding-out effect of foreign aid outweighs the preventive effect in the case of storms, while there is mixed evidence in the case of floods and earthquakes.